Adsorpsi Cu2+ Menggunakan Nanofiber Polisulfon-FeOOH Yang Disintesis Dengan Metode Elektrospinning - Adam, Dini Hariyati; Suyani, Hamzar; Nasir, Muhamad; Safni, Safni; Nugraha, Willy Cahya (Institution for Industrial Research and Standardization of Industry - Padang, 2013)
It had been done a research about adsorption of Cu2+ using polysulfone-FeOOH nanofiber prepared by elektrospinning method. Polysulfone-FeOOH nanofiber was synthesized by dissolving polysulfone pellets in 30 mL dimethylacetamide (DMAc). The effects of process conditions such as concentration, distance between the nozzle and collector, voltage and flow rate on the morphology and diameter of nanofibers were investigated. The optimum conditions of polysulfone nanofiber synthesizing was obtained with concentration 25%, distance 12 cm, voltage 25 kV, and flow rateÂ 0.05 mL/min with average diameters of fibers was 762.927 nm. Polysulfone nanofiber was coated with FeOOH to increase the adsorbtion capacity of Cu2+. The results showed that optimum condition for removal of Cu2+ used polysulfone-FeOOH nanofiber was obtained in 2 hours contact time, pH 6, adsorbent dosage 25 mg, and concentration of Cu2+ 10 mg/L with adsorbstion capacity was 9.79 mg/g, while for polysulfone nanofiber the adsorption capacity was 8.34 mg/g. The adsorbtion pattern of Cu2+ by the both of adsorbent followed the Freundlich isotherm pattern.ABSTRAK Penelitian mengenai pemisahan ion Cu2+menggunakan nanofiber polisulfon-FeOOH yang disintesis dengan metode elektrospinning telah dilakukan. Nanofiber polisulfon P-3500 disintesis dengan cara melarutkan pelet polisulfon ke dalam 30 mL dimethylacetamide (DMAc). Pengaruh kondisi seperti konsentrasi, jarak nozzle dengan kolektor, tegangan dan laju alir terhadap morfologi dan diameter serat dipelajari. Kondisi optimum pembuatan nanofiber polisulfon diperoleh dengan konsentrasi 23 %, jarak 12 cm, tegangan 25 kV, dan laju alir 0,05 mL/min dengan ukuran diameter serat rata-rata 762,927 nm. Nanofiber yang terbentuk dilapisi dengan FeOOH untuk meningkatkan kapasitas penyerapannya terhadap ion Cu2+. Dari hasil penelitian didapatkan kondisi optimum untuk pemisahan ion Cu2+ menggunakan nanofiber polisulfon-FeOOH yaitu waktu kontak 2 jam, pH 6, bobot adsorben 25 mg, dan konsentrasi Cu2+10 mg/L dengan kapasitas penyerapan 9,79 mg/g, sedangkan untuk nanofiber polisulfon kapasitas penyerapan 8,34 mg/g. Pola penyerapan Cu2+ untuk kedua jenis adsorben lebih sesuai dengan pola isoterm FreundlichÂ